2013
DOI: 10.5223/pghn.2013.16.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Inflammation and Diet

Abstract: Obesity is a state in which there is an over-accumulation of subcutaneous and/or abdominal adipose tissue. This adipose tissue is no longer considered inert and mainly devoted to storing energy; it is emerging as an active tissue in the regulation of physiological and pathological processes, including immunity and inflammation. Adipose tissue produces and releases a variety of adipokines (leptin, adiponectin, resistin, and visfatin), as well as pro- and anti-inflammatory cytokines (tumor necrosis factor-α, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
199
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(209 citation statements)
references
References 74 publications
2
199
1
7
Order By: Relevance
“…Pro-inflammatory cytokines, including TNF-α, produced by adipose tissues have been implicated as active participants in the development of obesity-related cardiovascular diseases (Hajer et al, 2008). Currently, obesity is regarded as a state in which chronic low-grade inflammation persists in adipose tissues (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, including TNF-α, produced by adipose tissues have been implicated as active participants in the development of obesity-related cardiovascular diseases (Hajer et al, 2008). Currently, obesity is regarded as a state in which chronic low-grade inflammation persists in adipose tissues (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, exogenous or endogen fatty acid as well as exogenous lipopolysaccharide are capable of inducing inflammation in adipose tissue through the activation of toll-like receptors present in both adipocytes and macrophages. However, the factors produced by the adipose tissue, both hormones and cytokines, have effect over other cell types including lymphocytes, dendritic cells, and neutrophils among others, affecting different mechanisms related with the production and release of multiple cytokines of the innate and adaptive response [16,17,33] (Figure 4). Now, the functionality of the adipose tissue under obesity condition have gained considerable interest mainly by its relationship with different diseases including diabetes, cardiovascular disease, metabolic syndrome, and its possible association with joint diseases [34,35].…”
Section: Relationship Among Adipokines and Immune Systemmentioning
confidence: 99%
“…Resistin is a hormone implicated in resistance of insulin, and visfatin is a hormone with implication in the utilization of glucose. However, these hormones also are implicated in inflammation process and they can interact with cells of the innate and adaptive immune system modulating the production of cytokines from adipocytes and the stromal-vascular fraction [16,17] (Figure 3). …”
Section: Hormonesmentioning
confidence: 99%
“…The intake of polyunsaturated acids was inversely associated with biomarkers of inflammation (C-reactive protein [CRP], interleukin [IL]-6, and TNF-α), while intake of trans and saturated acids was positively associated with levels of CRP and IL-6. 53 Wei et al studied the relationship between food and psoriasis in 646 psoriasis subjects and 647 healthy controls. 54 Results showed that alcohol consumption, spicy foods, and fat-rich meat were risk factors for psoriasis (P,0.01), while protein-rich meat and vegetable oil were protective factors (P,0.01).…”
Section: Dietmentioning
confidence: 99%